2007
DOI: 10.1152/ajprenal.00496.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic mercury interacts with cysteine residues (C451 and C474) of hOCT2 to reduce its transport activity

Abstract: Human organic cation transporter 2 (hOCT2) is essential for the renal tubular secretion of many toxic organic cations. Previously, of the cysteines (C437, C451, C470, and C474) that occur within transmembrane helices that comprise the hydrophilic cleft (proposed site of substrate binding), only C474 was accessible to maleimide-PEO(2)-biotin (hydrophilic thiol-reactive reagent), and covalent modification of this residue caused lower transport rates (Pelis RM, Zhang X, Dangprapai Y, Wright SH, J Biol Chem 281: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…We routinely use CHO cells as an expression system to study OCT2 transport (e.g., Suhre et al, 2005;Pelis et al, 2007Pelis et al, , 2012Harper and Wright, 2013). However, it is more common to use HEK293 cells as an expression for studying OCT-mediated transport (Nies et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We routinely use CHO cells as an expression system to study OCT2 transport (e.g., Suhre et al, 2005;Pelis et al, 2007Pelis et al, , 2012Harper and Wright, 2013). However, it is more common to use HEK293 cells as an expression for studying OCT-mediated transport (Nies et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…HEK293 cells were grown in Dulbecco's modified Eagle's medium with 10% fetal bovine serum with 100 mg/ml blasticidin. Cells that stably expressed OCT2 were prepared using methods described previously (Pelis et al, 2007). The OCT2-expressing cells were grown and maintained under hygromycin pressure (100 mg/ml) in plastic cell culture flasks at 37°C in a humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to PAH, MeHg also markedly decreased uptake of an organic cation, TEA, by kidney slices in all dietary groups. Although the exact mechanism behind this is not clear, inorganic mercury ion has been shown to interact with cysteine residues of human organic cation transporter 2 (hOCT2), and reduce hOCT2-mediated transport of TEA into Chinese hamster ovary cells stably expressing hOCT2 (Pelis et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…10). Recently, it was shown that cysteine 451 in human OCT2 was accessible to modification by HgCl 2 that was added to the extracellular side of the plasma membrane (25). The authors concluded that cysteine 451 resides in the aqueous milieu.…”
Section: Discussionmentioning
confidence: 99%